Potential Development of Vehicle Traction Levitation Systems with Magnetic Suspension - A.V. Kireev; N.M. Kozhemyaka; G.N. Kononov (Institute of Advanced Engineering and Science, 2015)
Below is given the brief analysis of development trend for vehicle traction levitation systems with magnetic suspension. It is presented the assessment of potential development of traction levitation systems in terms of their simplicity. The examples are considered of technical solutions focused on reducing the complexity of transport systems. It is proposed the forecast of their further development.